Electronic cigarette smoking as a health risk factor for modern adolescents - O.V. Dobrianska (Zaslavsky O.Yu., 2018)
Background. In our country, the reduced prevalence of usual cigarette smoking among the adolescents and the increased prevalence of alternative types of smoking, particularly the electronic cigarettes, is established. That is why the study on the prevalence of electronic cigarette smoking among the adolescents is a topical issue. The purpose was to study the prevalence of electronic cigarette smoking among the adolescents in Ukraine and to evaluate the influence of this type of smoking on adolescents' health. Materials and methods. In the article, we used the analytical, sociological, mathematic methods. The objects of study were 7-9 graders attending schools of different regions of Ukraine. In the frame of Global Youth Tobacco Survey (2017), we performed the questioning of the students. The survey was carried out using questionnaire unified for all World Health Organization countries. The questionnaire included a set of questions regarding electronic cigarette smoking. The total number of respondents was 4,065. Results. According to the results of Global Youth Tobacco Survey (2017), the share of electronic cigarette smokers is 18.4 % (among them, boys - 22.6 %, girls - 14.0 %) which is 2 times higher as compared to that of usual cigarette smokers - 9.2 % (boys - 10.8 %, girls - 7.7 %). We also determined the regional peculiarities of the prevalence of electronic cigarette smoking among the children: the highest level of electronic cigarette smoking was in Kyiv and Eastern region of the country, the lowest - in the Western and Northern regions. Conclusions. The lack of fundamental studies of the electronic cigarette impact on the children's health, the absence of law legislation determining age limitations of using these electronic devices can be considered as a threat for public health.